IMPLEMENTATION OF A MEDIA-ASSISTED THREE STEP INTERVIEW TYPE COLLABORATIVE LEARNING MODEL VIDIO TO IMPROVE LEARNING OUTCOMES CLASS STUDENT THAHARAH MATERIALS VII SMPN 4 KUALA: IMPLEMENTATION OF A MEDIA-ASSISTED THREE STEP INTERVIEW TYPE COLLABORATIVE LEARNING MODEL VIDIO TO IMPROVE LEARNING OUTCOMES CLASS STUDENT THAHARAH MATERIALS VII SMPN 4 KUALA - ANSARI AAN (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
ABSTRACT Learning aims to obtain results in three aspects, namely cognitive, affective and psychomotor. The cognitive aspect is knowledge that is measured by giving questions related to the material being taught. So that learning outcomes can be achieved well, it is necessary to have teaching methods that are relevant to the material being taught. One of the learning models and media that is relevant to thaharah material is the Three-Step Interview assisted by video media. This research aims to determine the effect of implementing the Three-Step Interview model assisted by video media on the learning outcomes of thaharah material for class VII students at SMPN 4 Kuala. This research uses a quantitative approach and experimental research type. Sample of 22 people. Data collection techniques were carried out using tests (pre-test and post-test). The data analysis technique uses a formula to calculate the mean and frequency distribution. From the results of the research, it can be seen that student learning outcomes are known from the pre-test scores, there are 15 students who have not completed the KKM score, with an average of 57.2% and this increases to 95.45% at the post-test stage. Thus, it can be said that the Three-Step Interview learning method assisted by video media plays a very important role in improving students' abilities in solving learning problems. Keywords: Collaborative Learning Model, Three Step Interview, Video Media, Learning Results, Tharah.